Hermite–Hadamard type inequalities involving fractional integrals of exponentially convex functions - Malik, Danish; Jabeen, Zamrooda (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We derive multiple inequalities employing exponential kernels in the context of fractional integrals. Within the framework of fractional calculus techniques, we explore novel Hermite–Hadamard type and Hermite–Hadamard–Fejér type inequalities applied to exponentially convex functions. These results provide valuable insights into the properties of exponentially convex functions and demonstrate the significance of fractional calculus in their analysis.